2014
DOI: 10.1016/j.jcat.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis design of Cu-SAPO-18, a very efficient catalyst for the SCR of NOx

Abstract: catalysts.-Complete framework Si isolation can be achieved for Cu-SAPO-18 materials.-Cu-SAPO-18 shows high catalytic activity and hydrothermal stability for SCR of NOx. KeywordsOne-pot synthesis, silicoaluminophosphate, SAPO-18, selective catalytic reduction (SCR), nitrogen oxides (NOx) 4 1.-IntroductionIn the last decades, small pore zeolites containing large cavities in their structure have become important industrial catalysts for the methanol-to-olefins (MTO) process, and for the field of gas separation.[1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 33 publications
4
43
0
Order By: Relevance
“…Our group reported that Cu‐SAPO‐44 exhibits excellent activity and N 2 selectivity over the wide temperature window from 200 to 550 °C . Because of the similar double six‐ring (D6R) structure in AEI and CHA zeolites, AEI‐type Cu‐SSZ‐39, Fe‐SSZ‐39, and Cu‐SAPO‐18 zeolites have been developed and exhibit excellent low‐temperature activity and high hydrothermal stability. Picone et al.…”
Section: Current Zeolite‐based Nh3‐scr Materialssupporting
confidence: 87%
“…Our group reported that Cu‐SAPO‐44 exhibits excellent activity and N 2 selectivity over the wide temperature window from 200 to 550 °C . Because of the similar double six‐ring (D6R) structure in AEI and CHA zeolites, AEI‐type Cu‐SSZ‐39, Fe‐SSZ‐39, and Cu‐SAPO‐18 zeolites have been developed and exhibit excellent low‐temperature activity and high hydrothermal stability. Picone et al.…”
Section: Current Zeolite‐based Nh3‐scr Materialssupporting
confidence: 87%
“…The work targeted the synthesis of Cu-SAPOs, because of their relevance to selective catalytic reduction, but investigation of one-pot synthesis using Ni 18 in this work from that of Corma and co-workers [12] is that whereas a template, N,N-dimethyl-3,5-dimethylpiperidinium, is used in that work to direct the synthesis of the SAPO-18, entraining Cu 2+ and/or Cu 2+ complex at the same time, in our synthesis it is the Cu-232 complex that directs crystallisation of the AEI structure.…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers reporting the direct synthesis of Cu-SSZ-13, [7] Cu-SAPO-34 [9][10][11] and Cu-SAPO-18 [12] using Cu The main difference between the method of synthesis in this work from that of Corma and co-workers, [12] is that whereas a template, N,N-dimethyl-3,5-dimethylpiperidinium, is used in that work to direct the synthesis of the SAPO-18, entraining Cu 2+ and/or Cu 2+ complex at the same time, in our synthesis it is the Cu-232…”
Section: Spectroscopic Characterisation Of Copper and Nickel Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been described the direct synthesis of Cu-SSZ-13 [13] and other related Cu-containing silicoaluminophosphate materials, such as Cu-SAPO-34 [12d, [14]] and Cu-7 SAPO-18, [15] using the combination of an organometallic Cu-complex (Cu-TEPA) and a cooperative organic molecule as OSDA. Following a similar "one-pot" synthesis procedure combining Cu-TEPA and N,N-dimethyl-3,5-dimethylpiperidinium as cooperative OSDAs, a crystalline Cu-containing SSZ-39 material has been achieved (see supporting information for experimental details and the PXRD pattern of Cu-SSZ-39 in Figure 1).…”
Section: +mentioning
confidence: 99%